Investigation of a New Sebum Control Cream Containing Apple Juice Extract - M. Shoaib Khan, Haji; Akhtar, Naveed; Rasool, Fatima; Madni, Asadulllah; Saeed, Tariq; A. Khan, Barkat; Mahmood, Tariq (Asian Journal of Chemistry, 2011)
Some polyphenols are considered useful to reduce sebum production. The objective of this study is to evaluate of stable water in oil skin caring cream (W/O emulsion), containing 3 % apple juice extract (rich in polyphenols), on sebum contents of skin in healthy male volunteers and compared it with base (without apple juice extract). Concentrated apple juice extract (Malus domestica) was entrapped in the inner phase of water in oil emulsion. Formulation containing apple juice extract and base containing no extract was formulated and subjected to different storage conditions to check their stability for a period of 4 weeks. Then both the formulation and base were applied to the cheeks of healthy human volunteers (n = 12) twice in a day for a period of 10 weeks. Sebum level on the both cheeks was determined with device (Sebumeter) before application of cream and during the study period. Every volunteer was asked to fill the performa about sensory evaluation of base and formulation at the end of study. A cream (base and formulation) was very well accepted by all volunteers. There was a significant reduction in sebum level. Statistically significant (p £ 0.5 %) result was found for skin sebum production by the formulation containing apple juice extract (3 %). This result shows the efficacy of sebum tested cream to reduce the greasiness and improve the appearance of oily facial skin. The new topical product was ideal in all aspects and can be used in skin disorders like acne for further investigation.